Pendampingan Pelaksanaan Permohonan Mandiri Terkait Administrasin Kependudukan Pada Aplikasi KNG (Klampid New Generation) Di Kelurahan Simomulyo - Lukman Arif; Nabila Riyadiana (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Population Administration (Adminduk) is an activity related to the arrangement and control of population registration and issuance of population documents through the Civil Registry Office. The role of the adminduk in state development is manifested in the planning of national development policies and programs as well as the realization of the civil rights of people who own population documents. With that, the Department of Population and Civil Registration has created an innovative administrative service, namely the KNG (Klampid New Generation) application. The introduction of this system will make it possible to help with online population administration. Management that has to come from below also makes people bored and finally chooses not to care about population administration as it should. Therefore, community assistance is carried out with independent applications regarding population documents through the KNG application and also provides an understanding regarding the requirements for independent applications for population documents that you wish to submit. The location of this research was conducted in Simomulyo Village, Sukomanunggal District, Surabaya City. Which aims to regulate the awareness of the residents of the Simomulyo Village to take care of or apply for population administration. It is hoped that with the assistance for submitting independent applications, it can make the community do it easily, effectively and quickly.